Peran Kelompok Wanita Tani ( KWT) di Tanjung Pinang - Anisha Avazura; Olla Meldi Wasyifa; Pasika Utami; Ratna Sari; Risma Selvi Dewi (Institut Nalanda, 2024)
Food safety can be implemented by optimizing outdoor space, namely: planting sustainable food crops. In addition, outdoor land can increase the role of farmer income reducing consumer spending and environmental sustainability. For research purposes, it is used to describe the role of women farmers and the obstacles faced by their group. The survey method is used as a research method with primary and secondary data. The group of women farmers consisted of 1 person, and one of the respondents we interviewed was the KWT manager. One of KWT’s tasks is to plant various vegetables such as spinach, kale, green beans, limes, etc. Vegetables grown at the market are also sold every two weeks by groups of women farmers and sold online. The government is also involved in women’s farming groups, such as donating money to KWT. Apart from its mission, there are several obstacles such as rotten beans during planting due to rain, and rotten beans having to be thrown away because they cannot be planted. Recycle.